Keindahan Saja’ Dalam Matan Tuḥfah Al-Aṭfāl Karya Sulaimān Al-Jamzūrī - Zahrotul Qotrunnada; Sayyed Zuhdi Abdil Ghany; Iin Suryaningsih (Mantiqu Tayr: Journal of Arabic Language, 2024)
The Arabic language serves as a global communication tool and is the principal language for 2 billion Muslims across the globe. Within Arabic, there are diverse realms of discourse and academic pursuits. One such domain is the Science of Badīʿ, a branch of Balāghah (rhetoric). A key area within the Science of Badīʿ delves into the resemblance of the final letters of two words at the conclusion of Arabic sentence structures. This resemblance, termed "sajaʿ," enhances the elegance of pronunciation, a pivotal facet of Balāghah. This research endeavors to explore this aesthetic dimension within the text of Tuḥfah Al-Aṭfāl, authored by Imam Sulaimān Al-Jamzūrī, a foundational work in Tajwid, the science of Quranic recitation. Employing a qualitative methodology with a descriptive-analytical approach, this study utilizes the Badīʿ theory as an analytical framework. The findings of this research reveal that the text of Tuḥfah Al-Aṭfāl embodies the grace of sajaʿ, which manifests in three distinct categories: muṭarraf, muraṣṣaʿ, and mutawāzī. This aesthetic quality proves invaluable for both students and educators, aiding in the memorization and comprehension of Tuḥfah Al-Aṭfāl within an educational context. Furthermore, it enriches the experience for general readers, allowing them to appreciate the beauty of its expression. Despite these insights, further research is essential to explore other dimensions of beauty present in Tuḥfah Al-Aṭfāl beyond sajaʿ. Additionally, investigating the element of sajaʿ beauty in various Arabic literary works would provide a more comprehensive understanding of its significance.